THE IDENTICAL VALUE BETWEEN CONSTITUTION AND CONSTITUTIONAL LAW IN THE CONSTITUTIONAL SYSTEM - Munir, Sirajul (Jurnal IUS, 2014)
The views of constitutional experts in modern government,Â there are three very important elements of the principles of government power in a country,Â namely the principles of the rights of citizens and the principle of the relationship between citizens and government,Â as well as the principles of governmental power (the principles According To the Government). This is described in the constitution to whom powers of state organizer submitted,Â whether the power will be given to the one hand/ institution or given to several State institutions who run these power. The principles of the rights of citizens (The Principles According to The Rights of The governed),Â in principle rights owned of citizen an integral part to be valued/ respected by a ruler. Then the principles of the relationship between citizens and government (The Principles According to the Relations Between The Government and The Governed),Â In these principle should be known of each rights and obligations between the citizens and government. Besides,Â the Constitution understood as a term to describe the overall system of Government of a country,Â as well as a collection of rules that establish and regulate or define Government in the country concerned. Thus encountered a two-dimensional understanding given as follows: first,Â the Constitution is the overall picture of the system of Government in a country (The Whole System of Government A Country) that the Constitution describes whether the form of State and system of Government in use. Second,Â the Constitution is a set of rules that establish and govern a countryâs Government (The Collection Of Rules Which Regulate or Establish and Govern The Government) it means in this second dimension,Â the Constitution is a set of rules about how the implementation of the overall system of Government of a country and a set of rules as the basis for the Division of power between the institutions of the State,Â the both dimension is a unity in the sense of the constitution or basic laws.Keyword: The Indonesian government system constitution is identical